EFFORTS TO IMPROVE DISCIPLINE STUDENTS THROUGH CHARACTER STRENGTHENING IN SMA NEGERI 9 YOGYAKARTA - Jumadi Jumadi (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2021)
This study aims to improve the discipline of students at SMA Negeri 9 Yogyakarta. The character of students at SMA Negeri 9 Yogyakarta is in a good category. If appropriately managed, this character has the potential to positively affect the discipline of students. This research was conducted in SMA Negeri 9 Yogyakarta. This research was conducted in 2 cycles. The development of this Best Practice is focused on improving student discipline through Strengthening Character Education (PPK) in SMA Negeri 9 Yogyakarta with details of the number of male students at SMA Negeri 9 Yogyakarta is 213 people, equivalent to 37.50% and female students totaled 355 people. Or the equivalent of 62.50%. The observation sheet in this research instrument will use a checklist. Best practice activities have succeeded in improving student discipline by strengthening character education (PPK) at SMA Negeri 9 Yogyakarta. This is evidenced by an increase in students' average discipline developing optimally, namely from class X, XI, and XII. From the initial conditions, it is still low or has not developed optimally. In Cycle I, there was an increase compared to the initial conditions before corrective action, namely with the criteria starting to develop, only class XI changed to class X and XI, and class XII developed as expected, in cycle II, action had an increase compared to cycle I, in cycle I all class X and XI began to develop. Class XII developed according to expectations, turning into class X developing according to expectations, and class XI and XII developing very well. In contrast, the assessment criteria began to develop and had not developed yet.